Health care-associated native valve endocarditis: importance of non-nosocomial acquisition - Benito, N.; Miro, J.M.; de Lazzari, E.; Cabell, C.H.; del Rio, A.; Altclas, J.; Commerford, P.; Delahaye, F.; Dragulescu, S.; Giamarellou, H.; Habib, G.; Kamarulzaman, A.; et al. (2009)
Background: The clinical profile and outcome of nosocomial and non-nosocomial health care-associated native valve endocarditis are not well defined. Objective: To compare the characteristics and outcomes of community-associated and nosocomial and non-nosocomial health care-associated native valve endocarditis. Design: Prospective cohort study. Setting: 61 hospitals in 28 countries. Patients: Patients with definite native valve endocarditis and no history of injection drug use who were enrolled in the ICE-PCS (International Collaboration on Endocarditis Prospective Cohort Study) from June 2000 to August 2005. Measurements: Clinical and echocardiographic findings, microbiology, complications, and mortality. Results: Health care-associated native valve endocarditis was present in 557 (34) of 1622 patients (303 with nosocomial infection 54% and 254 with non-nosocomial infection 46%). Staphylococcus aureus was the most common cause of health care-associated infection (nosocomial, 47%; non-nosocomial, 42%; P = 0.30); a high proportion of patients had methicillin-resistant S. aureus (nosocomial, 57%; non-nosocomial, 41%; P = 0.014). Fewer patients with health care-associated native valve endocarditis had cardiac surgery (41% vs. 51% of community-associated cases; P < 0.001), but more of the former patients died (25% vs. 13%; P < 0.001). Multivariable analysis confirmed greater mortality associated with health care-associated native valve endocarditis (incidence risk ratio, 1.28 95% CI, 1.02 to 1.59). Limitations: Patients were treated at hospitals with cardiac surgery programs. The results may not be generalizable to patients receiving care in other types of facilities or to those with prosthetic valves or past injection drug use. Conclusion: More than one third of cases of native valve endocarditis in non-injection drug users involve contact with health care, and non-nosocomial infection is common, especially in the United States. Clinicians should recognize that outpatients with extensive out-of-hospital health care contacts who develop endocarditis have clinical characteristics and outcomes similar to those of patients with nosocomial infection. Primary Funding Source: None.